Correlation of Hypovitaminosis D with Decompensated Chronic Liver Disease: A Cross-Sectional Study - Dr. R. K. Patel; Dr. D. P. Lakra; Dr. C. S. Sharma; Dr. Gurkirat Arora (International Journal of Pharma and Bio Sciences, 2023)
Hypovitaminosis D, an insufficiency or deficiency of vitamin D, can affect men and women across the lifespan. This fat-soluble vitamin affects mineral metabolism and numerous other physiologic functions. Chronic liver diseases (CLD) cause significant morbidity and mortality worldwide. The use of a biomarker such as 25-hydroxyvitamin D, indicates the severity of the disease, its complications and serves as a tool for early intervention. The present study was conducted with an objective to study the correlation of hypovitaminosis D in Decompensated Chronic Liver Disease and its clinical significance in Tertiary Care Hospital. The present study was an observational cross-sectional study carried out at the Department of Medicine of the tertiary care centre during November 2021 to October 2022. A total sample size of 60 patients with decompensated Chronic Liver Disease admitted in hospital was included in the study population. Vitamin D insufficiency is defined as 25 (OH) D level below 75 nmol/L (30 ng/mL) and deficiency as levels below 50 nmol/L (20 ng/mL). The outcome variables included levels of hypovitaminosis D in chronic liver disease patients, MELD score and Child Pugh Score. The statistical software namely SPSS 22.0 used for the analysis of the data. The mean age of the study population was 45.03 ±10.94 years. Majority of the patients were males (86.67%) Majority of patients with liver disease were with Vitamin D deficiency (76.67%) MELD score increases with vitamin deficiency and shows significant statistical association. The correlation of Vitamin D with MELD score and Child Pugh score shows significant strong negative correlation. This study was concluding that the Hypovitaminosis D is prevalent in chronic liver disease. CLD is associated with a significantly low level of vitamin D which was independent to gender.